2016
DOI: 10.1177/1060028016668627
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Outcomes of a Delirium Protocol in the Surgical Trauma Intensive Care Unit

Abstract: The implementation of a delirium protocol with nonpharmacological and pharmacological interventions had an impact on STICU patients experiencing acute delirium by significantly increasing delirium-free days and reducing the ICU LOS, in addition to decreased administration of concomitant medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The length of hospital stays among patients with delirium was four days longer on average, and ICU stay lengths 24 hours longer, than for patients without delirium. Other studies on postoperative delirium have shown that the average length of stay for spine surgery patients was three days or longer [6,8,10], the average for hip surgery patients was two days or longer [9], the average for cardiac surgery patients was four days or longer [12], the average for acute care surgery patients was seven days or longer [4], and the average for surgical trauma ICU and major surgery patients was four days or longer [21,22]. The length of hospital stays tends to increase with post-operative delirium status.…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stays among patients with delirium was four days longer on average, and ICU stay lengths 24 hours longer, than for patients without delirium. Other studies on postoperative delirium have shown that the average length of stay for spine surgery patients was three days or longer [6,8,10], the average for hip surgery patients was two days or longer [9], the average for cardiac surgery patients was four days or longer [12], the average for acute care surgery patients was seven days or longer [4], and the average for surgical trauma ICU and major surgery patients was four days or longer [21,22]. The length of hospital stays tends to increase with post-operative delirium status.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 27 included studies, 11 were RCTs or randomized pilot studies [21, 28, 29, 31-33, 35, 39-41, 45], eight were pre-post prospective studies [23,25,36,37,43,44,46,47], two were quasi-experimental [22,27], and the remaining six were a case-matched control study, an evidence based protocol, a mixedmethods pilot study, a prospective cohort study, a retrospective cohort study, and an action research study [24,26,30,34,38,42].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining nine bundle studies developed new, unique bundles. They included four pre-post studies [25,43,46,47], three RCTs [32,33,40], one quasi-experimental study [22], and one action research study [30]. Seven assessed delirium incidence and duration using CAM-ICU [22,25,30,32,40,46,47], one used NEECHAM [33], and one used ICDSC [43].…”
Section: Other Bundled Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac effects are rare where cumulative daily doses of intravenous haloperidol are lower than 2 mg, unless patients have additional risk factors for QTc prolongation (Meyer‐Massetti et al, ). Studies indicate significant benefit where care of delirious patients is protocolised to include dose titration with regular monitoring of arousal, cardiac status and for EPS (Skrobik et al, ; Dale et al, ; Sullinger et al, ). However, implementation is challenging—a survey of ICU specialists found that QTc monitoring was highly variable, not routinely measured in 20% of ICUs and haloperidol continued in 60% cases where QTc interval exceeded 500 ms (Devlin et al, ).…”
Section: Introductionmentioning
confidence: 99%